Shear-induced Permeability Evolution of Sandstone Fractures. (23rd December 2018) - Zhang, Hongwei; Wan, Zhijun; Feng, Zijun; Wu, Jinwen
Abstract : In underground coal mines, shear-induced changes in regional fluid flow are a major factor causing water inrushes from faults into working faces. Shear slip along preexisting fractures tends to be activated during hydraulic fracturing, and this movement can either enhance or diminish hydraulic fracturing efficiency. To prevent water inrush disasters and further hydraulic fracturing, understanding the evolution of shear-induced permeability in fractures in sedimentary rock is very important. In this study, the evolution of shear-induced permeability in saw-cut sandstone fractures with three different types of surface roughness was investigated by conducting triaxial shear tests and examining the 3-D topography of the unsheared and sheared fracture surfaces. The results allow several important conclusions to be drawn. (1) The permeability of fractures follows a three-stage shear-displacement-dependent evolution. The permeability remains unchanged in the first stable stage. After that, permeability decreases sharply with increasing shear displacement. Finally, the permeability enters a second stable stage. (2) The shear stress versus shear-displacement curves can also be divided into three stages, namely, a stress adjustment stage, a stage of increasing stress, and a stable stage. During the experiments, the fractures always experienced stick-slip shear in the stable stage. The oscillations of the shear stress in the stick-slip stage had a higher frequency for fractures with rougher surfaces. In addition, the rougher surfaces exhibited a greater permeability drop after shearing than that shown by smoother fracture surfaces. (3) The 3-D scanning results imply that the coupled effects of grinding (plus scraping) and sealing lead to decreased permeability. During shearing, the fracture walls grind and scrape against each other resulting in partial flattening of the fracture surface and the production of fault gouge in the fracture. This leads in turn to the flow pathways being partially sealed by crushed mineral grains.